Farming with Hugh Martin #49 - tobacco (Kingston : Jamaica Information Service (JIS), 1980)
The farming and processing of tobacco.
No sound.
Recorded on May 14, 1980.
Also available as an electronic reproduction.
Keywords: Agriculture -- Jamaica; Tobacco -- Jamaica; Tobacco industry -- Jamaica; Agriculture -- Jamaica; Tobacco. -- Jamaica